PSIDIUM GUAJAVA L. EXTRACT INCREASES PLATELET COUNT THROUGH ENHANCEMENT OF STEM CELL FACTOR EXPRESSION IN THROMBOCYTOPENIC MICE MODEL - Atik, Nur; Tarawifa, Susan; Avriyanti, Erda; Rahmadi, Andri Reza; Hilmanto, Dany (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: The purpose of this study was to determine the mechanism through which guava extract increases platelet count. Methods: Twenty male Swiss webster mice were divided into 4 group. Group I received 2.8 mg/20 g body weight of quinine and 1 ml of distilled water. Group II received 2.8 mg/20 grBW of quinine and 0.785 mg/20 grBW of guava extract. Group III received 1 ml distilled water and 0.785 mg/20 grBW of guava extract and Group IV only received 1 ml distilled water. After 14 days** treatment, platelet count was measured using Raas-Ecker method. SCF and TPO mRNA expressions in mice liver were assessed using qRT-PCR. Results: The data showed that quinine administration reduced platelet count significantly (P<0.05). Psidium guajava L. extraction significantly enhanced platelet count in mice that were treated with quinine compared with quinine group (p<0.05). The mechanism was analysed further and our RT PCR data showed that stem cell factor mRNA expression significant increased (p<0.05) in quinine plus guava extract group compared to quinine group. Conclusion: It indicated guava extract role in increasing megakaryopoiesis which resulted in an increase of platelet count.Â 